谐波齿轮传动系统非线性扭转振动仿真软件设计 - 辛洪兵; 秦宇辉 (Jixie chuandong)
The harmonic drive system nonlinear torsional vibration behaviors analysis software,which integrated the principle of harmonic drive,the theory of nonlinear dynamics,the numerical analysis method and the technology of computers,has been developed.New transmission error formula,new nonlinear torsional stiffness formula and backlash are considered in this model.The software has Windows GUI style and facility for operation features.It is special for study on the nonlinear dynamics behaviors of harmonic drive system.Experimental results for a harmonic drive reducer with type of XB-80-134H verify the effectiveness of the software.Simulation results can be used as a reference for design and experimental analysis.